Analisis Peran Audit Internal dalam Menjaga Kepatuhan Prinsip Syariah pada Bank Syariah - Elsi Nuliawati Marpaung; Muhaammad Syafril Nasuiton (Indonesia Economic Journal, 2026)
The rapid growth of the Islamic banking industry demands an effective oversight system to ensure that all operational activities are conducted in accordance with Sharia principles. Sharia compliance is a fundamental aspect that serves as the primary distinction between Islamic banks and conventional banks, and is a key factor in building public trust. In this context, internal audit plays a strategic role as a supervisory mechanism tasked with evaluating, monitoring, and ensuring the bank’s operational compliance with Sharia provisions, banking regulations, and Sharia governance principles. This study aims to analyze the role of internal audit in maintaining Sharia compliance at Islamic banks and to identify various factors influencing the effectiveness of its implementation. The study employs a qualitative method using a literature review approach, examining various scientific journals, academic articles, and relevant literature from the past five years. The results of the study indicate that internal audit plays a crucial role in ensuring Sharia compliance through its oversight functions regarding the implementation of contracts, evaluation of compliance with DSN-MUI fatwas, fraud prevention, risk mitigation, and the strengthening of Sharia governance implementation. The effectiveness of internal audit is influenced by auditor competence, auditor independence, management support, and coordination